Male Gatekeepers Gender Bias in the Publishing Process? - Felix Bransch; Michael Kvasnicka (Institute of Labor Economics (IZA), 2017)
Using data on articles published in the top-five economic journals in the period 1991 to 2010, we explore whether the gender composition of editorial boards is related to the publishing success of female authors and to the quality of articles that get published. Our results show that female editors reduce, rather than increase, the share of articles that are (co-)authored by females. We also find evidence that female editors benefit article quality at low levels of representation on editorial boards, but harm article quality at higher levels. Several robustness checks corroborate these findings. Our results are broadly consistent with existing evidence on the behavior of gender-mixed hiring committees and of relevance for gender equality policy.
Keywords: A14; J16; J71; 330; gender bias; citations; journals; editors